A novel fluorescence and surface-enhanced Raman scattering dual-signal probe for pH sensing based on Rhodamine derivative. (November 2015) - Ma, Pinyi; Liang, Fanghui; Wang, Di; Yang, Qingqing; Yang, Zhaoqin; Gao, Dejiang; Yu, Yong; Song, Daqian; Wang, Xinghua
Abstract: A reversible off-on-type probe for pH sensing with fluorescence and surface-enhanced Raman scattering (SERS) dual-signal output, Rhodamine–phenanthroline (RGP), was designed and synthesized from Rhodamine 6G and 1, 10-phenanthroline. Due to the molecular structure transformation between spirocyclic and ring-open forms, RGP exhibits varying fluorescence and SERS activities at different pH levels. The values of acidity constants ( pK a ) and fluorescence quantum yield ( Φ ) of RGP were 2.43 (±0.14) and 0.48, respectively. The fluorescence change of RGP was reversible and took place mainly within the pH range from 1.0 to 4.0. The SERS signals of RGP could be stable more than 3 h under room temperature and with little loss of efficiency after the pH of the sample solution was switched between 3.29 and 6.09 for 5 times. Most of the common inorganic ions and polycyclic aromatic hydrocarbons (PAHs) in water samples have little influence on the analytical performance of the probe. The present probe is simple and easy-to-use for the pH sensing in acidic media. Graphical abstract: A novel fluorescence and SERS dual-signal probe for pH sensing of acidic samples was developed based on RGP, a Rhodamine derivative which could transform the molecular structure between spirocyclic and ring-open forms at different pH levels. Highlights: A novel dual-signal probe for pH sensing of acidic samples was developed. Dyes with both dual-signal output for pH sensing is the first time reported. The present probe is simple and easy-to-use for the pH sensing in acidic media. The probe is applicable for pH sensing of environmental samples.